229 Dysregulated axonal homeostasis in C9orf72 iPSC-derived motor neurones. Issue 12 (14th November 2019) - Mehta, Arpan; Selvaraj, Bhuvaneish; Dando, Owen; Burr, Karen; Hardingham, Giles; Chandran, Siddharthan
Abstract : Dysregulated axonal homeostasis is a potential pathomechanism in ALS, but its relevance to the commonest known genetic mutation in ALS – the C9orf72 repeat expansion – remains unclear. We performed unbiased transcriptomics of cell-autonomous C9orf72 motor neurone (MN) perturbations in a humanised model using patient-derived induced pluripotent stem-cell lines against an isogenic background generated by CRISPR/Cas9 and studied the functional consequences of downstream axonal hits. Differential gene expression analysis examined the intersection in differentially expressed genes between the mutant-isogene pairs, revealing 215 genes: 95 up and 120 down. Pathway analysis showed an axonal signature, with upregulation of pathways involved in cytoskeletal organisation, axon guidance, and Trk receptor signalling, and downregulation of pathways involved in the mitochondrial electron transport chain and axon guidance. Significantly dysregulated genes were confirmed using real-time quantitative PCR. This led to two hypotheses examining for aberrations in axonal length and transport. Axonal length was measured using manual tracking of SMI-312 labelled axons. Axonal transport was determined by tracking Ds-Red2 labelled mitochondrial movement using a live-imaging setup and analysed using KymoToolBox. Both axonal length and transport were reduced in the mutants compared to their isogenic counterparts. Further experiments are underway to determine whether common pharmacological manipulations can rescue both phenotypes.